The role of private pesticide vendors in preventing access to pesticides for self-poisoning in rural Sri Lanka. Issue 2 (4th June 2013) - Weerasinghe, Manjula; Pearson, Melissa; Peiris, Ravi; Dawson, Andrew H; Eddleston, Michael; Jayamanne, Shaluka; Agampodi, Suneth; Konradsen, Flemming
Abstract : In 15% to 20% of self-poisoning cases, the pesticides used are purchased from shops just prior to ingestion. We explored how pesticide vendors interacted with customers at risk of self-poisoning to identify interventions to prevent such poisonings. Two strategies were specifically discussed: selling pesticides only to farmers bearing identity cards or customers bearing pesticide 'prescriptions'. Vendors reported refusing to sell pesticides to people thought to be at risk of self-poisoning, but acknowledged the difficulty of distinguishing them from legitimate customers; vendors also stated they did want to help to improve identification of such customers. The community did not blame vendors when pesticides used for self-poison were purchased from their shops. Vendors have already taken steps to restrict access, including selling low toxic products, counselling and asking customer to return the next day. However, there was little support for the proposed interventions of 'identity cards' and 'prescriptions'. Novel public health approaches are required to complement this approach.